Face and stereotyped notions about Chinese face behavior.[article]. - Ho, David Y. F.
The present paper investigated both Chinese and Western views of face. It attempted to answer two questions; (1)Is face behavior is unique to distinctive of the Chinese and other peoples who have been influenced by them, or it is a universal phenomenon? (2)What are the factors which have contributed to the formation of the stereotype that, as a people, Chinese attach an overriding importance top face? After a critical review of both Chinese and Western literature, the following conclusions were reached: (a)serious conceptual and methodological difficulties (specifically ethnocentric bias) are often present, even in studies reported in the social science literature, which render the validity of the investigators' conclusions ambiguous and suspect; (b)there is a consensus of opinion that the rituals of face behavior operate to avoid confrontation and to conserve the traditional Chinese socio-political structure characterized by the dominance of vertical authority relationships; and (c)observers are unanimously agreed that Chinese attach great importance to face although there is disagreement on whether or not this is unique to them. Upon further study of this point of disagreement, it was concluded that the Chinese are simply more conscious of the significance of face in social processes than are other peoples. This greater awareness on the part of the Chinese was partly traced to their language, which has been richly endowed with symbolic representations of face behavior since early history. It was further pointed out that is might be more meaningful, conceptually, to study the variation in face behavior in different cultural contexts, rather that to try to show which ethnic groups attach a greater degree of importance to face.